Administration of Dydrogesterone in first trimester of pregnancy will increase the level of PlGF (Placental Growth Factor) - Dewi K. Rusly; Kanadi Sumapraja; . Rajuddin; Kartini Hasballah (Syiah Kuala University, 2013)
Early placental development can be determined by measuring placental growth factor or Placental growth factor (PlGF) through the mother's blood since the first trimester of pregnancy. The purpose of this study was to determine the effect of supplementation on the development didrogesteron placenta in pregnancy by measuring the levels of PlGF. This study is a randomized double-blind clinical trial (Randomized Controlled Clinical Trial) held at the Antenatal Clinic (ANC) at the General Hospital dr. Zainoel Abidin (RSUZA), Banda Acehto women of reproductive age in the first trimester in RSUZA ANC checkup. Nonprobability sampling sampling with consecutive sampling. In this study there were two groups of women of reproductive age who are not in pairs is given didrogesteron group A while group B received placebo. Measurement of PlGF levels in both groups performed before and after treatment. PlGF levels prior to treatment in Group A 25.95 pg/ml while Group B 40.80 pg/ml. PlGF levels after the measurement results given didrogesteron in Group A for 4 weeks gainedincreasing levels of PlGF is 212.15 pg/ml, whereas in group B were given a placebo for 4 weeks was 89.60 pg/ml. Data analysis was performed using bivariate analysis between supplementation didrogesteron and PlGFlevels using SPSS 17. Analysis of data for comparative analytical numerical information unpaired two groups: Group A: the results of a PlGF levels in pregnant subjects were given didrogesteron and Group B: the results ofa PlGF levels in pregnant patients given placebo. Unpaired t-test results of the two groups showed that the group receiving didrogesteron have elevated levels of PlGF were significantly (p = 0.000 or p 0.05) compared with the placebo group were only given alone. From these results it can be concluded that the administration can trigger didrogesteron PlGF levels in women of reproductive age.